Clinicopathological profile of hoarseness of voice - Rathi, Abhinav; Sharma, Shalaka (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
Background: Hoarseness of voice is one of the most common symptoms bringing a patient to an ear, nose and throat (ENT) Out Patient Department (OPD). Hoarseness of voice may arise from wide spectrum of diseases ranging from mild infections to fatal malignancies. Hence a study was done to know the incidence, etiology, predisposing factors and clinical profile of patients presenting with hoarseness of voice. Methods: The study was carried out in the Department of ENT, JNU IMSRC, Jaipur from Aug 2017 to July 2018. All the patients coming to ENT OPD with complaint of hoarseness of voice during that period underwent detailed history, clinical examination and routine investigations to know the exact cause of hoarseness. Results: A total of 126 cases with male:female ratio of 1.68:1 were analyzed. Patients age ranged from 13 to 82 years with majority of patients presenting in 4th decade. Most commonly hoarseness was seen in labourers (42.06%) with most common cause being vocal cord paralysis (23.01%) and majority of patients having smoking as the commonest predisposing factor (65%). Conclusions: The etiology of hoarseness varies from trivial infections to serious malignancies. In our tertiary centre which is at the outskirts of the city majority of the patients coming to OPD are from rural area and most of these patients are labourers by occupation and have a habit of smoking bidis.